Polymetallic Complexes, Part XLIX: Synthesis Magnetic and Spectral studies of Co(II), Ni(II), Cu(II), Cu(II), Zn(II), Cd(II) and Hg(II) Complexes with Donor Bis-Azodye Ligands - B. Mahapatra, Bipin; Pradhan, S.P. (Asian Journal of Chemistry, 2010)
Both the bis-azodye ligands, bis [4, 4´–(8´-hydroxyquinolyl-5´)-azophenyl] methane and bis [4, 4´-(8´-hydroxyquinolyl-5´)–azo-phenyl] sulphone form dinuclear complexes with divalent metal ions. The Co(II) and Cu(II) complexes are either octahedral or distorted octahedral, both the Ni(II) complexes are square planar and the Zn(II), Cd(II) and Hg(II) complexes are tetrahedral in configuration basing upon analysis, conductance, magnetic moments, IR, electronic, ESR and NMR spectral studies.